THE RELATIONSHIP BETWEEN THE WORK ENVIRONMENT AND JOB SATISFACTION OF NURSE ANESTHETISTS IN HOSPITALS, CENTRAL JAVA-BALI - Ni Nyoman Ari Kundari Dewi; I Ketut Swarjana; IGNM Kusuma Negara; Yustina Ni Putu Yusniawati (Nurse and Health: Jurnal Keperawatan, 2023)
Background: Nurse anesthetists as medical personnel have an important role in the continuity of work in the operating room. Although they have considerable responsibility and role, no research has focused on the job satisfaction of nurse anesthetists. In addition, no literature review has shown low job satisfaction among nurse anesthetists. Objectives: This research aimed to determine the relationship between the work environment and job satisfaction of nurse anesthetists in hospitals. Methods: This research used a quantitative method with a cross-sectional design through an online survey. The population of this research covered all nurse anesthetists working in hospitals in Central Java and Bali, of which 108 respondents were selected as the sample using a simple random sampling. The data were collected using questionnaires and analyzed using inferential statistics, namely chi-square, to determine the relationship between the work environment and job satisfaction of nurse anesthetists. Results: This research showed that a total of 60 respondents (55.6%) had a high category of job satisfaction. In addition, the work environment factor (p=<0.001) significantly affected the job satisfaction of nurse anesthetists. Conclusion: Hospital management must strengthen the commitment related to the sense of belonging to employees by considering the work environment factor that can affect the job satisfaction of nurse anesthetists in hospitals.